Buddhayana: Memahami Peran Ashin Jinarakkhita dalam Pengembangan Spiritual Umat Buddha - apriyanto, rio; Anjani, Dia; Burmansah, Burmansah; Tupari, Tupari (Kajian dan Reviu Jinarakkhita: Jurnal Gerakan Semangat Buddhayana (Jinarakkhita Review & Studies: Journal of Buddhayana Spirit Movement), 2023)
Spiritual development among Indonesian Buddhists has received a strong boost through the role of Ashin Jinarakkhita, in the course of his dedicated life, Ashin Jinarakkhita has become a major pillar in enriching the spiritual experience of Indonesian Buddhists. Her teachings and practices have influenced many individuals, leading them on a journey towards a deeper understanding of Buddhism. This article will review this pivotal role, exploring the various ways in which Ashin Jinarakkhita has contributed to strengthening the spiritual and religious foundation of Indonesian Buddhists. This research utilizes the library research method to collect secondary data related to Ashin Jinarakkhita's role. The results of this research show that Ashin Jinarakkhita has become an important pillar in the spiritual development of Indonesian Buddhists. Over the course of his life, Ashin Jinarakkhita has been dedicated to spreading Buddhism, providing spiritual guidance, and establishing places of worship and Buddhist education. In addition, his role in promoting peace, interfaith tolerance, and moral leadership has helped strengthen the spiritual and ethical foundation of Indonesian Buddhist society